PENGEMBANGAN KOMIK SEBAGAI MEDIA PEMBELAJARAN BERBASIS CTL (CONTEXTUAL TEACHING AND LEARNING) MATERI PENCEMARAN LINGKUNGAN KELAS X - Elma Erviana; HRA Mulyani; Muhfahroyin Muhfahroyin (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2022)
Developement of this teaching material produced products in the form of biology teaching materials in the form of learning comics, and comics as learning media based on Contextual Teaching and Learning (CTL). This environmental pollution material was expected to help in the learning process and can motivate students to be more active in studying environmental pollution materials. Based on interviews with class X teachers of SMA Negeri 5 Metro regarding the learning media used. The class X teacher said that the problems experienced in the learning process were that there were still many students who got scores below the minimum completeness criteria (KKM) of 60. The method used in development was the Research and Development (R&D) method with the model development with a 4-D model, there were“four stages, namely Define, Design, Develop, and Disseminate. The data from the material expert validation obtained a percentage value”of 84% with the